1980
DOI: 10.1111/j.1943-278x.1980.tb00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Offender‐Victim Relationships in Criminal Homicide Followed by Offender's Suicide, North Carolina, 1972–1977

Abstract: An analysis of 90 cases of criminal homicide followed by suicide in North Carolina, 1972 to 1977. Homicidal victim-offender relationships were investigated in regard to age, sex, race and whether victim and offender were member of the same family, friends, acquaintances, or strangers. These results were compared with victim-offender relationships in 994 criminal homicide cases in North Carolina in which offenders did not commit suicide. Married white males over 30 years were much more involved in homicide-suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 2 publications
3
60
0
Order By: Relevance
“…It is interesting that it has been claimed that homicide-suicide perpetrators are more like suicide-only individuals than like those who only engage in homicidal behavior (e.g., [6][7][8][9]). Although this is true in relation to suicide variables, there certainly is a pattern of distinct difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting that it has been claimed that homicide-suicide perpetrators are more like suicide-only individuals than like those who only engage in homicidal behavior (e.g., [6][7][8][9]). Although this is true in relation to suicide variables, there certainly is a pattern of distinct difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, it has been reported that homicide-suicide perpetrators share more characteristics with suicide-only than homicide-only perpetrators [6][7][8][9]. However, the differences between those who engage in spousal/consortial, familial and extrafamilial homicide-suicides may be marked.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In 2002, Finland had a suicide rate of 32.3/ 100,000 for males and 10.2/100,000 for females, while the respective rates for Estonia were 47.7/100,000 and 9.8/100,000, respectively [4]. Previous research has suggested that homicide-suicide perpetrators share more characteristics with those who commit suicide than with those who commit homicide [12][13][14][15]. These studies used the relationship between the victim and the perpetrator as a measure.…”
Section: Introductionmentioning
confidence: 98%
“…Investigating the epidemiology of abnormal homicide and murder followed by suicide, Coid [8] found rates of about 0.20-0.30/100,000. According to Palmer and Humphrey [9] about 2% of criminal homicide cases are followed by the suicide of the offenders in North Carolina.…”
Section: Introductionmentioning
confidence: 99%